Decolonizing Feminism: From Reproductive Abuse to Reproductive Justice - Stote, Karen (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
This paper asks why reproductive gains have sometimes amounted to reproductive abuse for Indigenous women in Canada. Guided by an intersectional and decolonial approach, it provides a historical material critique of the individualized rights discourse and reformist goals that tend to underlay feminist struggles in Canada. It explores how western feminism might support decolonization and reproductive justice.